2013
DOI: 10.3399/bjgp14x676401
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ knowledge, attitudes, and practice in childhood fever: an internet-based survey

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 18 publications
8
60
1
4
Order By: Relevance
“…However, referrals and multiple contacts within the system often resulted in dissatisfaction [37]. Parents indicated that antipyretics were used regularly to control fever symptoms [34,35,40,43,46]. Parents perceived that they knew how best to manage fever, yet non-evidence based practice was observed in the included studies.…”
Section: Summary Of Narrative Synthesismentioning
confidence: 96%
See 3 more Smart Citations
“…However, referrals and multiple contacts within the system often resulted in dissatisfaction [37]. Parents indicated that antipyretics were used regularly to control fever symptoms [34,35,40,43,46]. Parents perceived that they knew how best to manage fever, yet non-evidence based practice was observed in the included studies.…”
Section: Summary Of Narrative Synthesismentioning
confidence: 96%
“…Parents' knowledge of fever varied widely [42]. Parents demonstrated a fear of fever, directly related to negative outcomes associated with fever such as febrile convulsions [34,43]. Parents who received safety netting advice were less likely to re-present to urgent and emergency care services [37].…”
Section: Summary Of Narrative Synthesismentioning
confidence: 96%
See 2 more Smart Citations
“…1 As many parents work during the day and fever typically rises in the early evening, these rates are even higher during out-of-hours care. 1,2 In most cases, fever is caused by benign viral infections, and general recommendations given by a family physician are sufficient for management. 3 One in every 3 to 4 children who visit family physician out-of-hours care with a fever receives an antibiotic prescription, however.…”
Section: Introductionmentioning
confidence: 99%